ANALISIS TINGKAT KESADARAN MASYARAKAT DESA TARIKAN KECAMATAN KUMPEH ULU KABUPATEN MUARO JAMBI DALAM MEMBAYAR ZAKAT HASIL PERTANIAN - Qurrata Ayunin; Bambang Kurniawan; Muhammad Ismail (Lembaga Pengembangan Kinerja Dosen, 2023)
The aims of this study are: (1) To determine the effect of knowledge about zakat on public awareness in paying zakat (2) To determine the effect of public awareness level on the number of those who pay zakat (3) To determine the effect of agricultural potential, especially plantations on public awareness in pay zakat. This study uses quantitative methods. The method of data collection is through a questionnaire (questionnaire), observation, documentation. This is done by collecting data in the form of numbers. The data in the form of numbers are then processed and analyzed to obtain scientific information behind the figures. The data used in this study were obtained from the results of distributing questionnaires to 76 respondents as a data collection tool. This study uses data analysis techniques that use simple linear regression to determine the magnitude of the X variable to the Y variable, as well as to test the hypothesis to determine the magnitude of the influence of each variable. After being analyzed using SPSS, it can be concluded that there is a positive but not significant effect between the independent variable (level of public awareness) on the dependent variable (paying zakat) where in the examiner based on the results of the t test (table 4.13) that the tcount value is 1.688 > ttabe, 1668 and the value Significant 0.096> 0.05 then H0 is accepted and Ha is rejected.